Penanaman 1000 Pohon dalam Upaya Meningkatkan Kesadaran Masyarakat tentang Penghijaun Lingkungan di Desa Mbuju - Rahmat Hidayat; Fatmawati; Kabunggul, Yuliantri; Kristina Lo; Najmah; Siti Hasmawati (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Tree planting is a form of environmental preservation that needs to be cultivated starting from the environment around Mbuju village through the reforestation movement by planting 10,000 trees consisting of manghuni, white teak, rambutan, jackfruit, durian, chocolate, avocado which involves in this activity community service students and youth youth organizations such as babinsa, babinka, community leaders and local communities. It is hoped that the movement of 10,000 trees will be able to create the first step in public awareness to care about the environment. Greening can also change the weather, namely by absorbing carbon dioxide to produce oxygen through the photosynthetic process carried out by the trees. planted to improve air quality and prevent the impact of global warming. The method used is observation or survey. The conclusions from the implementation of the greening program for planting 1000 trees are: (1) Campus stakeholders, in this case students and lecturers at Muhammadiyah University, collaborate with the government, youth organizations and residents of Mbuju village to be directly involved in the program by planting 1000 jackfruit, soursop and rambutan trees. , guava, and durian; (2) The tree planting program has been implemented well, namely planting more than 1000 tree seedlings of jackfruit, soursop, rambutan, guava and durian trees in the spring area of Mbuju.